2015
DOI: 10.1111/cmi.12499
|View full text |Cite
|
Sign up to set email alerts
|

TheToxoplasma gondiirhoptry protein ROP18 is an Irga6‐specific kinase and regulated by the dense granule protein GRA7

Abstract: SummaryIn mice, avirulent strains (e.g. types II and III) of the protozoan parasite Toxoplasma gondii are restricted by the immunity‐related GTPase (IRG) resistance system. Loading of IRG proteins onto the parasitophorous vacuolar membrane (PVM) is required for vacuolar rupture resulting in parasite clearance. In virulent strain (e.g. type I) infections, polymorphic effector proteins ROP5 and ROP18 cooperate to phosphorylate and thereby inactivate mouse IRG proteins to preserve PVM integrity. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 50 publications
(127 reference statements)
4
77
0
Order By: Relevance
“…These in vitro studies suggest that in vivo GRA7 acts to increase turnover of IRGs, thus displacing them from the PV membrane and making monomeric substrates available for phosphorylation by ROP18. Other studies confirm that GRA7 is needed for maximum activity of ROP18 against the substrate Irga6 in infected cells (43), perhaps reflecting the enhanced turnover described above together with the close physical proximity of ROP18 and GRA7, which form a large complex in the cell (5). ROP5 and ROP18 also contribute to the ability of virulent strains of T. gondii to avoid recruitment of GBPs to the PV membrane; these appear to act downstream of IRGs in the control of intracellular…”
Section: Targeting Of Host Innate Immunitymentioning
confidence: 85%
“…These in vitro studies suggest that in vivo GRA7 acts to increase turnover of IRGs, thus displacing them from the PV membrane and making monomeric substrates available for phosphorylation by ROP18. Other studies confirm that GRA7 is needed for maximum activity of ROP18 against the substrate Irga6 in infected cells (43), perhaps reflecting the enhanced turnover described above together with the close physical proximity of ROP18 and GRA7, which form a large complex in the cell (5). ROP5 and ROP18 also contribute to the ability of virulent strains of T. gondii to avoid recruitment of GBPs to the PV membrane; these appear to act downstream of IRGs in the control of intracellular…”
Section: Targeting Of Host Innate Immunitymentioning
confidence: 85%
“…The localization of IRGs to the PVM can be inhibited mainly through the ROP5/17/18 complex . In addition, GRA7 can bind to oligomers of Irga6, acting synergistically with ROP18 to control the localization of IRGs onto the PVM, although deletion of GRA7 has not or slightly increased the IRGs’ recruitment . We wondered whether GRA12 and ROP18 act in a complex to target IRGs, likewise GRA7.…”
Section: Discussionmentioning
confidence: 99%
“…PVM‐localized effector proteins are secreted from two major organelles: the dense granule (GRA) and the rhoptry (ROP), which subvert the host cellular functions by interacting with the PVM to protect T. gondii against host deleterious defense and clearance mechanisms, or crossing the PVM and translocating to nucleus to regulate the gene expression . The kinase ROP18 and pseudokinase ROP5 function together to inactivate host immunity‐related GTPase (IRGs) by phosphorylation, thereby preventing degradation of the PV and promoting parasite survival in mice . GRA18 traffics across the PVM to reach the cytoplasm of infected host cells where it forms complexes with host components of the β‐catenin destruction complex to regulate the host gene expression in a β‐catenin‐dependent fashion .…”
Section: Introductionmentioning
confidence: 99%
“…GRA7 contributes to inhibition of vacuolar IRG protein accumulation at the PVM and is Irga6 specific. It has been demonstrated that T. gondii GRA7 as a regulator of ROP18-specific inactivation of Irga6 in vivo (49). The structural diversity of the IRG proteins implies that certain family members constitute additional specific targets for other, as-yet-unknown, T. gondii virulence effectors.…”
Section: Discussionmentioning
confidence: 99%